2017
DOI: 10.18203/2394-6040.ijcmph20175352
|View full text |Cite
|
Sign up to set email alerts
|

A study of knowledge and practice of breast feeding in urban slum area under urban health centre in Solapur city, Western Maharashtra

Abstract: INTRODUCTIONAs per UNICEF global databases 2015, globally only about two fifth of children benefit from exclusive breast feeding. Percentage of children worldwide put to the breast within one hour of birth is 44%. Exclusively breastfed (0-6 months) is 39%; children's receiving solid, semi-solid or soft foods (6-8 months) is 65% and continuing to be breastfed at 1 year is 74%. Continued breast feeding up to 2 years (20-24 months) is 49%.1 In India though breastfeeding is nearly universal, very few children begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 1 publication
1
9
2
Order By: Relevance
“…This nding was higher than the study ndings in Bennatsemay woreda (45.7%), and Nairobi city (49.5%) (22,23). On the other hand, this nding was lower than the study ndings in Shebele Zone, in India and Solapur city (24)(25)(26). This inconsistency might be due to time gap between studies and difference in the study settings; since the current study was done among mothers in with lower socio economic status whereas the former studies included mothers in the Woreda with better socio economic characteristics.…”
Section: Factors Associated With Mothers' Knowledgecontrasting
confidence: 62%
See 2 more Smart Citations
“…This nding was higher than the study ndings in Bennatsemay woreda (45.7%), and Nairobi city (49.5%) (22,23). On the other hand, this nding was lower than the study ndings in Shebele Zone, in India and Solapur city (24)(25)(26). This inconsistency might be due to time gap between studies and difference in the study settings; since the current study was done among mothers in with lower socio economic status whereas the former studies included mothers in the Woreda with better socio economic characteristics.…”
Section: Factors Associated With Mothers' Knowledgecontrasting
confidence: 62%
“…Mother's attitude about IYCF practices was less evidenced than the general knowledge base. In a similar study (26), 82.2% mothers had a positive attitude about EBF (24). On the contrary, other study did not nd a desirable attitude of mothers towards IYCF practices even though the mothers perceived good knowledge.…”
Section: Factors Associated With Mothers' Knowledgementioning
confidence: 89%
See 1 more Smart Citation
“…Similar finding was observed by Patel et al 15 A total 64.25% mothers were having knowledge regarding duration of exclusive breastfeeding in our study, whereas, in study conducted by Rajput et al it was 57.25%. 16 Maximum numbers of mothers i.e. 89% were nonworking and 11% were working in our study.…”
Section: Discussionmentioning
confidence: 67%
“…However, in study conducted by Rajput RR it was 92.75% and 7.25% of participants were nonworking and working respectively. 16 Authors found on demand breastfeeding in 55% of participants. However, in study conducted by Mise et al it was 60.7%.…”
Section: Discussionmentioning
confidence: 99%